Workers' Voice in platform labour: An Overview - Heiner Heiland (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2020)
This study documents various forms of worker representation and attempts to establish them in platform labour in Europe. Different types of fragmentation of platform workers are analysed, which lead to workers' silence and make representation unlikely. Against this background, a broad spectrum of workers' voice forms that are prevalent and emerging in platform labour is examined. The study thus provides an overview of the current state of research and presents challenges and perspectives for workers' voice. The project is part of the European research network "Hybridisation of Work", which is organized by the Economic and Social Science Institute (WSI) of the Hans-Böckler-Foundation.
urn:nbn:de:101:1-2020102613561185731705
Keywords: 330